Pelatihan Aplikasi Artificial Intelligence (AI) Bagi Siswa Jurusan Rekayasa Perangkat Lunak Pada Sekolah Menengah Kejuruan (SMK) 3 Selong - Muh. Adrian Juniarta Hidayat; Yupi Kuspandi Putra; Yahya; Liana Rozita Muzarrofah (Jurnal Teknologi Informasi untuk Masyarakat, 2026)
The development of artificial intelligence (AI) technology provides opportunities to increase the effectiveness and productivity of learning in the field of software engineering. However, some students still lack adequate knowledge and skills in utilizing AI applications to support the learning process of programming and software development. This community service activity aims to improve the competence of students of the Software Engineering Department of SMKN 3 Selong in using AI applications as learning aids and software development. The method used is Participatory Learning and Action (PLA) which actively involves participants through material delivery, demonstrations, hands-on practice, and discussion sessions. The results of the activity show that participants are able to understand the basic concepts of AI and utilize various AI applications to help find programming solutions, create program codes, documentation, and design software. In addition, participants demonstrated improved skills in completing software development tasks more effectively and efficiently. This activity provides benefits in the form of increased technological literacy, learning productivity, and student readiness to face technological developments and the needs of the software industry that increasingly utilizes artificial intelligence.